Adjunctive inhaled amikacin in infants with Ventilator-Associated Pneumonia optimizes the complex antimicrobial therapy: pilot study: Adjunctive inhaled amikacin in infants with VAP - Levchenko, Bohdan; Nazarchuk, Oleksandr; Dmytriiev, Dmytro; Bahniuk, Natalia; Melnychenko, Mykola; Dmytriiev, Kostiantyn (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: VAP remains the second leading cause of death among the patients with nosocomial infections and its incidence varies significantly from 5% to 60% reaching on average 10 %. It is of crucial importance to develop novel treatment approaches and optimize the existing ones. Thus, the aim of this pilot study was to study the laboratory-microbiological effect of inhaled aminoglycosides in a complex treatment of patients with ventilator-associatedpneumonia(VAP). Methods: To study the laboratory-microbiological effect of adjunctive inhaled aminoglycosides in the treatment of VAP, twenty enrolled patients were randomly subdivided into 2 groups (n=10). Amikacin was administered via a nebulizer starting from the first day of VAP manifestation. Inhalations were performed BID for 7 days via a nebulizer integrated into the breathing circuit. We assessed: cell membrane alterations in leukocytes, Annexin V/7-AAD staining for leukocytes, ROS detection assay for leukocytes. Results: Adjunctive administration of inhaled amikacin reduced the fluorescence intensity ratio more efficiently compared with the intravenous antimicrobial treatment with no aerosolized amikacin following both 48 h and 96 h of treatment. The amount of dead necrotic annexin V-negative, 7-AAD-positive leukocytes was significantly lower under the use of inhaled amikacin than at the beginning of treatment. Conclusions In this pilot study, we found that administration of aerosolized amikacin combined with the systemic antimicrobial therapy improves the clinical outcome of patients with VAP, effective early microbial decrease in the sputum, reduces reactive oxygen species generation in leukocytes and the degree of leukocyte apoptosis and necrosis, decreases VAP-mediated cell membrane alterations of circulating leukocytes.